2011
DOI: 10.1016/j.tourman.2010.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and economic development: The beach disease?

Abstract: This paper analyses empirically the danger of a Dutch Disease Effect in tourism-dependent countries in the long run. Data on 134 countries of the world over the period 1970-2007 is used. In a first step the long-run relationship between tourism and economic growth is analysed in a crosscountry setting. The results are then checked in a panel data framework on GDP per capita levels that allows to control for reverse causality, non-linearity and interactive effects. It is found that there is no danger of a Beach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(135 citation statements)
references
References 41 publications
11
121
1
2
Order By: Relevance
“…Conversely, [20] provided an empirical analysis to assess the long-run danger of a DD effect in tourism-dependent countries named "Beach Disease Effect" in [20]. This analysis concluded that there was no reason to fear a "Beach Disease Effect", at least in the long-run, and that most of the indirect effects of tourism should operate through physical and human capital channels.…”
Section: B Empirical Studiesmentioning
confidence: 99%
“…Conversely, [20] provided an empirical analysis to assess the long-run danger of a DD effect in tourism-dependent countries named "Beach Disease Effect" in [20]. This analysis concluded that there was no reason to fear a "Beach Disease Effect", at least in the long-run, and that most of the indirect effects of tourism should operate through physical and human capital channels.…”
Section: B Empirical Studiesmentioning
confidence: 99%
“…When more people visit the country attracted by the greenery and natural beauty there, it will result in revenue generation and hence can contribute to the economic growth of the country, e.g. Mehmood et al, (2014), Marrocu &Paci (2011), andHolzner, (2011). The increased GDP, in turn, can provide more opportunities for the enhancement of tourism by providing the financial assistance and proper management.…”
Section: Results and Interpretationsmentioning
confidence: 99%
“…Studies also show that tourism has significant positive effects on economic growth in EU countries (Holzner, 2011;Albalate & Bel 2010) suggesting that tourism enhances economic growth in the long run. Mihalic (2002) argues numerous benefit of tourism as a growing tactic via export of goods and services.…”
Section: Literature Reviewmentioning
confidence: 99%